The Current and future status of landscape education and research in Korea - Byoung-E Yang (Landscape Review, 1995)
SINCE REGULAR EDUCATION in landscape architecture in Korea began in 1973, landscape architecture departments have been established in 25 universities and in four junior colleges. Among the universities, six offer PhD programmes in landscape architecture. One of the issues that Korean landscape education faces is whether the goal of education should be directed toward generalist or specialist education. Other issues faced are how to fit education into professional practice and how to adjust education to meet changes in social demands. Contemporary theoretical and methodological issues in landscape education and research include: the need to infuse Korean tradition into contemporary landscape design; landscape impact assessment; and sustainable landscape planning and design. It is expected that future research will be focused on the development of new paradigms in landscape architecture. New types of landscape research will also emerge due to the changes in social demands over the next decade.